Abnormalities of tumor endothelial cells and cancer progression. Issue 1 (31st August 2017) - Hida, Kyoko; Maishi, Nako
Abstract: Tumor growth and metastasis are dependent on angiogenesis, which is the formation of new blood vessels. The newly formed blood vessels around the tumor supply oxygen and nutrients to the tumor, supporting its progression. Moreover, these blood vessels also serve as channels through which tumor cells metastasize to distant organs. The balance between angiogenic stimulators and inhibitors regulates angiogenesis in the tumor microenvironment. Tumor blood vessels, especially the endothelial cells lining tumor blood vessels (tumor endothelial cells [TECs]), are important targets in cancer therapy. As newly formed tumor blood vessels originate from pre‐existing normal vessels, tumor blood vessels and TECs have traditionally been considered to be the same as normal ones. However, tumor blood vessels have a distinctively abnormal phenotype, including morphological alterations. Recently, it has been revealed that TECs constitute a heterogeneous population, exhibiting characteristics that are largely induced by tumor microenvironmental factors. Furthermore, TECs induce cancer progression through metastasis. In this review, we describe recent studies on TEC abnormalities related to cancer progression and consider their therapeutic implications.